(untitled) (MMIT Proceedings, 2024)
The Belt and Road Initiative (BRI) is reshaping Uzbekistan through Chinese infrastructure and trade financing, but its sustained development effects are unclear. BRI improves regional connectivity, China-Uzbekistan trade, and Chinese renewable energy financing, according to studies. This project also brings new developments to Uzbekistan, including the development of the railway and logistics sectors and entry into international trade and markets. What is clear is that we must grow, and the few obstacles we meet can be conquered with success tactics.